Physician perspectives on traditional, complementary, and integrative medicine and the national evidence-based Japanese integrative medicine information website: A mixed-method study - Motoo, Yoshiharu (Integr Med Res, 2021)
BACKGROUND: The evidence-based Japanese integrative medicine (eJIM) website was launched by the Japanese government in 2014 to provide information on integrative medicine to the general public and physicians. While Japanese physicians discourage the use of traditional, complementary, and integrative medicine (TCIM), there are very few reports that explore this issue. We aimed to understand the attitudes of Japanese physicians towards TCIM and evaluate the usability of the eJIM website according to physicians. METHODS: We conducted a two-staged, mixed-method study with interviews and an internet-based survey. Face-to-face interviews were conducted with 12 physicians who worked for large-scale hospitals in two different areas of Japan. We assessed their understanding of TCIM and the usability of the eJIM website. Based on the interviews, the internet survey was developed and was conducted in February 2019. RESULTS: In the interviews, 12 physicians provided their opinion on TCIM and highlighted important areas, such as increasing the resources available for patients, and ensuring more information on TCIM is available. The internet survey of 231 physicians showed that 35% of the physicians used or advised on TCIM in clinical practice. Kampo medicines (87.8%) and dietary supplements (24.7%) were common. The physicians did not use TCIM primarily because of concerns regarding its efficacy, safety, and cost. Most physicians were not aware of which TCIM their patients used. CONCLUSION: Physicians in Japan may not have comprehensively understood TCIM and do not actively use TCIM. The eJIM website could help physicians to gain a better understanding of TCIM if improvements are made.